2012
DOI: 10.1097/jgp.0b013e31820eea0c
|View full text |Cite
|
Sign up to set email alerts
|

Social Emotion Recognition, Social Functioning, and Attempted Suicide in Late-Life Depression

Abstract: Objectives-Lack of feeling connected and poor social problem solving has been described in suicide attempters. However, cognitive substrates of this apparent social impairment in suicide attempters remain unknown. One possible deficit, the inability to recognize others' complex emotional states has been observed not only in disorders characterized by prominent social deficits (autism-spectrum disorders and frontotemporal dementia) but also in depression and normal aging. This study assessed the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
1
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 48 publications
(49 reference statements)
7
122
1
14
Order By: Relevance
“…These results call the attention to the fact that the degree of ToM impairment observed in psychiatric populations highly depends on the composition of the comparison groups. Other studies have described that certain clinical features of depression like suicidal behaviours [43] or anxiety [32] have a negative impact on RMET performance.…”
Section: Resultsmentioning
confidence: 99%
“…These results call the attention to the fact that the degree of ToM impairment observed in psychiatric populations highly depends on the composition of the comparison groups. Other studies have described that certain clinical features of depression like suicidal behaviours [43] or anxiety [32] have a negative impact on RMET performance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has posited that alexithymia may have a mediating role between impulsivity and emotional-behavioral functioning (Szanto et al, 2012). However, no other studies to my best knowledge have specifically investigated the relationship between impulsivity and alexithymia in adolescents with BED and their influence on adolescents' emotional-behavioral functioning.…”
Section: Purpose Of the Studymentioning
confidence: 85%
“…Loftis (2012) has studied the role of alexithymia and impulsivity in the suicidal behavior on young adults. The author found that when variables were included together in a regression model, only alexithymia remained statistically significant, suggesting that the presence of alexithymia was the stronger predictor of suicidal behaviors, connected to internalizing and externalizing problems (Szanto et al, 2012).…”
Section: Research Questionsmentioning
confidence: 99%
“…One candidate measure is social emotion recognition, which has recently been shown to characterize older adult suicide attempters. 15 …”
Section: Discussionmentioning
confidence: 99%
“…If suicidal risk was indeed less pernicious in this group, then we anticipated that those with Low Distress/Death Ideation would also score low in a known correlate of suicide risk, social isolation. 1415 We also predicted the presence of another group endorsing a passive wish to die: this group would not endorse active suicidal ideation, but would be at elevated risk for suicide due to the presence of clinically significant depressive and anxiety symptoms and high scores on both functional impairment and social isolation (i.e., a “High Distress/Death Ideation” group).…”
mentioning
confidence: 99%